Demographic, medical, and psychosocial predictors of benefit finding among caregivers of childhood cancer survivors. Issue 1 (22nd October 2015) - Gardner, Molly H.; Mrug, Sylvie; Schwebel, David C.; Phipps, Sean; Whelan, Kimberly; Madan‐Swain, Avi
Abstract: Background: There is a growing body of literature examining benefit finding, or finding positive outcomes in the face of adversity, among both adults and children with chronic conditions, and to some degree among caregivers. This study examined demographic, medical, and psychosocial predictors of greater benefit finding specifically among caregivers of childhood cancer survivors. Methods: Caregivers of children who had completed treatment for cancer ( n = 83) completed measures assessing child and caregiver demographic information and caregiver coping (active, acceptance, emotion‐focused, and avoidant), optimism, social support, caregiving burden, posttraumatic stress symptoms, illness impact (how much caregivers feel impacted by their child's illness in various domains), and benefit finding (positive outcomes). Result: Regression analyses indicated that positive spiritual coping, optimism, and illness impact uniquely predicted overall benefit finding for caregivers of childhood cancer survivors. Conclusion: Results point to adaptive tendencies that are associated with finding benefits when caring for a childhood cancer survivor and suggest potential avenues for intervention among this population. Copyright © 2015 John Wiley & Sons, Ltd.